THE EFFECTIVENESS OF SOCIAL MEDIA MARKETING (INSTAGRAM) AND WORD OF MOUTH ON THE DECISION TO CHOOSE STABN SRIWIJAYA UNIVERSITY - Pringgondani; Franky Okto Bernando; Andhyka Wicaksono (Universitas Muhammadiyah Bengkulu, 2025)
The purpose of this study is to examine how social media marketing, particularly Instagram, and word-of-mouth marketing affect students' decisions to enroll at Sriwijaya State Buddhist University (STABN). The study involved 200 randomly selected students from the second, fourth, sixth, and eighth semesters at STABN Sriwijaya, Tangerang, Banten. The survey approach was used, and the major tool was a questionnaire. With a computed t-value of 5,559 and a significance level of 0.000 <0.05, the initial hypothesis test findings from a population of 400 students demonstrate that social media marketing has a considerable impact on student decisions. With a t count of 11,775 and a significance level of 0.000 <0.05, the results of the second test also demonstrate a significant impact of word-of-mouth marketing. When the third hypothesis is tested, the estimated F value of 175.509 and the significance level of 0.000 <0.05 reveal that the two variables taken together have a substantial effect on student decisions. These findings suggest that word-of-mouth and social media marketing techniques play a significant role in luring students to STABN Sriwijaya.